Trends in Ambient Air Quality (NO2 and SO2) in Tenggarong City, Kutai Kartanegara District. East Kalimantan - SUJIMAN, Sujiman (International Journal of Environmental, Sustainability, and Social Science, 2023)
This research aims to determine the concentration of ambient air quality NO2 and SO2, determine the trend in ambient air quality NO2 and SO2, and determine the Air Quality Value index for Tenggarong City, Kutai Kartanegara Regency, East Kalimantan. The data collection method was using the 18-SPEKTRO-33/MU/SMM-AAS (Passive Sampler Spectrophotometry) method, then analyzed using environmental quality standards, government regulation number 22 of 2021. The research results show that the quality concentration of NO2 gas in Jam Bentong is between (5.23-19.85) µg/m3 and SO2 is between (3.75-38.55) µg/m3, in the Industrial Area NO2 is between (5.54-10.20) µg/m3 and SO2 is between (4.28 -10.41) µg/m3, while in residential locations NO2 is between (2.49-7.98) µg/m3 and SO2 is between (<2.57-10.60) µg/m3. The tendency for ambient air quality NO2 and SO2 at the Jam Bentong location to fluctuate is inconsistent, while the Industrial Location is almost the same as the Residential Location, namely with uniform quality, but all quality concentrations are still below environmental quality standards. The Environmental Quality Index value at the Jam Bentong location is 79,618, this value is included in good environmental conditions. Meanwhile, in industrial locations it is 90,043, this value is included in superior environmental conditions. Meanwhile, in residential locations, the Environmental Quality Index value is 93,429, this value also falls into superior environmental conditions.